Zariski Topology of Intuitionistic Fuzzy d-filter - Hasan, Ali Khalid (Iraqi Journal of Science, 2022)
In this paper we discuss the Zariski topology of intuitionistic fuzzy d-filter in d-algebra, with some topological properties on the spectrum of intuitionistic fuzzy d-filter in d-algebra X which have algebraic features such as connectedness. We find that this topology is a strongly connected, and  T0 space. We also define the invariant map on intuitionistic fuzzy prime d-filter with a homomorphism map.